The Health Belief Model and the Gluten-Free Diet: Are Gluten-Free Products Really Beneficial in Athlete Diets? - GÜNER, Demet; ÇILGINOĞLU, Hakkı (Spor Bilimleri Arastirmalari Dergisi, 2023)
People often think gluten-free products are healthier. This idea has been a source of motivation for many consumers, including athletes. With the growing popular perception that gluten-free foods are healthier, whether this diet is actually beneficial has had to be questioned. In the study, on the basis of the Health Belief Model, it was evaluated how the gluten-free diet was preferred among the athletes. With this study, it is aimed to contribute to the formation of awareness in athletes on this issue. Scientific publications published so far have been examined with a systematic literature search. 45 studies between the years 2012-2022 in Web of Science, Scopus and TR Index databases have been examined. “Are Gluten-Free Products Really Beneficial in Athlete Diets?” in all of the reviewed publications. The answer to the research question was sought. The data analyzed with the MAXQDA 2020 qualitative data analysis program were classified and interpreted by the content analysis method. The study was designed according to the ENTREQ control guideline. As a result of the sources examined, it has been determined that a gluten-free diet facilitates digestion, lowers cholesterol levels and reduces cardiovascular risks. However, it has been observed that the body is deficient in meeting the nutrients it needs. Studies conducted in various countries have shown that gluten-free products have poor content, especially in terms of protein and iron content that athletes need. Most of the obtained publications were compilation type. However, it is thought that case studies to be conducted with athletes who eat gluten-free in future studies will allow to discuss the subject from a different aspect.
Keywords: Turizm (Diğer); Tourism (Other); Athlete diet; Health belief model; Gluten-free diet; Gluten; Celiac; Spor Hekimliği; Sports Medicine